Primary Care Providers' Awareness of Physical Activity-Related Intensive Behavioral Counseling Services for Cardiovascular Disease Prevention. Issue 2 (February 2019) - Omura, John D.; Watson, Kathleen B.; Loustalot, Fleetwood; Fulton, Janet E.; Carlson, Susan A.
Purpose: The US Preventive Services Task Force recommends that adults at risk for cardiovascular disease (CVD) be offered or referred to intensive behavioral counseling interventions to promote a healthful diet and physical activity for CVD prevention. We assessed primary care providers' (PCPs) awareness of local physical activity-related behavioral counseling services, whether this awareness was associated with referring eligible patients, and the types and locations of services to which they referred. Design: Cross-sectional survey. Setting: Primary care providers practicing in the United States. Subjects: 1256 respondents. Measures: DocStyles 2016 survey assessing PCPs' awareness of and referral to physical activity-related behavioral counseling services. Analysis: Calculated prevalence and adjusted odds ratios (aORs). Results: Overall, 49.9% of PCPs were aware of local services. Only 12.6% referred many or most of their at-risk patients and referral was associated with awareness of local services (aOR = 2.81, [95% confidence interval: 1.85-4.25]). Among those referring patients, services ranged from a health-care worker within their practice or group (25.4%) to an organized program in a medical facility (41.2%). Primary care providers most often referred to services located outside their practice or group (58.1%). Conclusion: About half of PCPs were aware of local behavioral counseling services, and referral was associated with awareness. Establishing local resources and improving PCPs' awareness of them, especially using community–clinical linkages, may help promote physical activity among adults at risk for CVD.